Barrier-Lyapunov Function based Dynamic Surface Control of Quad-Rotorcraft. Issue 2 (2020) - Dasgupta, Ranjan; Roy, Sayan Basu; Bhasin, Shubhendu
Abstract: A novel framework is proposed in this paper for control of a quad-rotorcraft where hierarchical design is constructed via barrier Lyapunov function (BLF) combined with dynamic surface control (DSC). DSC solves the requirement of higher order differentiability of reference pose and avoiding the complexity that arises due to the "explosion of terms" coming out from repeated derivatives of reference attitude and desired thrust vector. BLF satisfies attitude constraint in real-time and thereby ensures non-singularity of velocity transformation leading to feasible control design. Stability analysis shows that all the signals in the closed-loop system are uniformly ultimately bounded and tracking error converges asymptotically. The performance of the BLF-based DSC is illustrated with a suitable example.